5‐Species MHD Study of Martian Proton Loss and Source. Issue 4 (9th April 2023) - Sun, Wenyi; Ma, Yingjuan; Russell, Christopher T.; Luhmann, Janet; Nagy, Andrew; Brain, David
Abstract: Although photochemistry‐enabled escape of oxygen is a dominant atmospheric loss process at Mars today, ion outflow plays an essential role in the long‐term evolution of Mars' atmosphere. Apart from heavy planetary ions such as O +, O2 +, and CO2 +, the loss of planetary protons is also important because it could be related to water loss. To study planetary proton loss due to solar wind interaction, we improve the 4‐species (O +, O2 +, CO2 +, and H + ) single‐fluid magnetohydrodynamic (MHD) model of Mars, to a 5‐species (separating planetary protons and solar wind protons) MHD model so that the two types of protons can be tracked separately. The global distributions of solar wind protons and planetary ions at low altitudes are investigated. The calculated planetary proton escape rates are larger than heavy ion loss rates and solar wind proton inflows for both solar maximum and minimum conditions. Planetary proton escape rates are 1–2 orders less than neutral hydrogen loss, suggesting that planetary protons could contribute to no >10% of the hydrogen loss under current conditions. By comparing normal cases with cases for which H‐O charge exchange reactions or electron impact ionizations are switched off, we find that H‐O charge exchange mainly affects densities at low altitudes, while impact ionizations exert great influence on escape rates at high altitudes. The overall results suggest the specific treatment of proton origins in models of Mars atmosphere escape provides better insight into the contributing processes, and should be included in future studies focusing on water's fate. Plain Language Summary: It is commonly believed that Mars has lost most of its atmosphere. While there are many works on the escape rates of heavy ions such as O +, O2 +, and CO2 +, there are few studying proton loss which is also important due to its relation to the loss of water. We separate the protons from the solar wind and protons originating in the planetary atmosphere, so that the 4‐species (O +, O2 +, CO2 +, and H + ) single‐fluid magnetohydrodynamic (MHD) model is improved to a 5‐species (separating planetary protons and solar wind protons) MHD model. The global distributions of solar wind protons and planetary ions at low altitudes are discussed. The calculated escape rates suggest that planetary proton loss is important compared with heavy ion loss and solar wind proton inflow, even though planetary proton loss is no >10% of previously estimated atomic hydrogen loss. We investigate the effects of two types of reactions where protons are involved: H‐O charge exchange and electron impact ionization. We find that impact ionization is important at high altitudes therefore also important for escape rates, while H‐O charge exchange mainly exerts influence at low altitudes. The total integrations of chemical reactions indicate their relative importance. Key Points: Solar wind protons and planetary protons are analyzed separately using the updated magnetohydrodynamic model Planetary proton loss is estimated to be larger than heavy ion loss, but 1–2 orders less than neutral hydrogen loss The effects of impact ionization and H‐O charge exchange reactions are quantified